Voices of youth: how Indigenous young people in urban Ontario experience plans of care - Madigan, Brittany (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2017)
The plan of care is a document completed regularly for every child and youth in the care of Children’s Aid Society in Ontario. Using a mixed methods approach with a strong emphasis on Indigenous Methodologies, a key informant and two Indigenous young people who have been in care share their thoughts about how plans of care can be improved. The youth describe how their plan of care was impacted by the relationship with their worker and level of participation in goal setting. It is discussed that the plan of care presents as a standardized, bureaucratic tool that does not inherently reflect Indigenous culture. These findings lead to recommendations for change including greater opportunities for relationship-building between workers and youth, space for young people to participate in planning, integration of Indigenous culture in plans of care, and the need for reconciliation at the macro level.